(3GdGfJUGQ dfbd GdbQBfs - (3eMeO Hf GdWjH Hf eMeO Hf LYaQ, Jbj GdOjf CHh HcQ, GdbGVj GdHGbdGfj , J (B403 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Pi GdbOQI hGdLdGd s
(3BNQgG (B:s
(3jfJgi CKfGA GdcdGe ai eYfi GdHjGf hgd gh GdHdGZI Hbhdg (B: (3aCeG GdHjGf HGdGTGQI abO bdfG ajg eG cai s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjOGfjI ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(1 / 374) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs